2020
DOI: 10.1103/physrevresearch.2.013114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanisms of kinetochore capture with varying number of spindle microtubules

Abstract: The biophysical mechanisms of kinetochore capture by spindle microtubules within cells are stochastic processes with a moving target searched by multiple walkers inside a confined volume. We study and compare two such mechanisms: dynamic instability-driven search and capture, common in many eukaryotes, and angular diffusion of pivoted microtubules reported in fission yeast. Characteristic times associated with the rare events of capture scale as a power law with the microtubule number, and their comparison pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…Our work indicates new avenues for understanding the nonequilibrium features of resetting, e.g., in the study of optimization of resetting pathways for efficient particle transport. Furthermore, we expect that our formalism could be extended to shed light on various biophysical problems described by onedimensional diffusion with suitable boundary and/or resetting conditions, such as microtubule dynamics [43,44], molecular motors [2,45,46], single-file diffusion of water in carbon nanorings [47], or polymer translocation through nanopores [48,49] In this Appendix, we report the solution for the Laplace transform of Eq. (1) for P(x, t|x 0 , x r ), the probability distribution of the Brownian particle position in one dimension, initially at x 0 , resetting to x r according the space-dependent resetting rate r c (x).…”
Section: Discussionmentioning
confidence: 99%
“…Our work indicates new avenues for understanding the nonequilibrium features of resetting, e.g., in the study of optimization of resetting pathways for efficient particle transport. Furthermore, we expect that our formalism could be extended to shed light on various biophysical problems described by onedimensional diffusion with suitable boundary and/or resetting conditions, such as microtubule dynamics [43,44], molecular motors [2,45,46], single-file diffusion of water in carbon nanorings [47], or polymer translocation through nanopores [48,49] In this Appendix, we report the solution for the Laplace transform of Eq. (1) for P(x, t|x 0 , x r ), the probability distribution of the Brownian particle position in one dimension, initially at x 0 , resetting to x r according the space-dependent resetting rate r c (x).…”
Section: Discussionmentioning
confidence: 99%
“…For any stochastic system, the first passage time is a random variable that denotes the first time some event occurred [23]. Examples of such events may be like a passive or active particle reaching a boundary [24,25], a protein binding to a specific patch on DNA [26], a moving kinetochore being captured by microtubules [27], or as in this case protein levels reaching a pre-determined threshold. The papers [21,22], showed that a model based on the statistics of first passage times to reach a critical protein concentration could reproduce the observed data.…”
Section: Introductionmentioning
confidence: 99%
“…Search and capture processes are ubiquitous in nature and have been an important topic in stochastic processes [1][2][3]. Such processes find application in a wide range of fields [4][5][6][7][8][9][10][11][12][13][14], and the list is still growing. Theoretical techniques to study a search and capture process involve the statistics of the first encounter with the target -commonly known as the first passage times (FPT).…”
Section: Introductionmentioning
confidence: 99%
“…While open space is relevant in many physical problems, on the other hand, there are many diffusive processes in nature that occur in confined spaces. Transport inside living cells are limited by the cellular dimensions -relevant examples in this context are proteins binding to a target site on DNA [45] or microtubules trying to capture a kinetochore [11]. Likewise, neutrophils chase and engulf diffusing bacteria or foreign particles within a finite region of the bloodstream [46].…”
Section: Introductionmentioning
confidence: 99%